Case Report on Chronic Actinic Dermatitis - Veedu, Arathi Thekke; Thomas, Tonya Clara; Shaijan, Gopika Konattu; Thazhayil, Maneesha; Karuvanvalappil, Kabeer Parayil (Journal of Pharmacy Practice and Community Medicine)
Chronic Actinic Dermatitis (CAD) or Chronic Photosensitivity Dermatitis is an immunologically mediated photodermatosis which is characterized by pruritic eczematous lesions, severely itchy, red, inflamed and thickened dry skin of sun exposed areas. The other term of chronic actinic dermatitis is Actinic reticuloid. It is usually seen in patients older than 50 years of age. The etiology of chronic actinic dermatitis is not identified until now. The diagnosis of chronic actinic dermatitis is based on patient history, cutaneous findings and histological features (biopsy). Photo protection measures are a central management of chronic actinic dermatitis. Other therapeutic remedies include immunosuppressive agents and antihistamines. Here we reported a case of chronic actinic dermatitis presenting with long history of itching and reddish lesions, multiple hyper pigmented and erythematous papules and plaques present over the body. On the scalp there is multiple well defined de-pigmented and erythematous plaques were present. The patient condition improved with the use of steroids, antihistamines and sunscreens.
Keywords: Chronic actinic dermatitis; Photodermatosis; Photoprotection; Photopatch; Photosensitive.